Adapting topeng the masked theatre of Bali Adapting topeng : an interview with John Emigh, Brown University, and excerpts from Little Red Riding Shawl - Emigh, John, 1941-; Michigan State University. Department of Theatre (East Lansing, Mich. : Instructional Media Center, Michigan State University, 1980)
Demonstrates adapting Topeng acting styles and techniques to Western productions. The program highlighted with humorous excerpts from Little Red Riding Shawl. In an interview from the West and from the masked theatre of Bali to develop the production
Title from title screen
Project director, Farley Richmond ; director Larry McMullin ; music arranged by Amy Callin
DVD format
Keywords: Theater -- Indonesia -- Bali; Masks -- Indonesia -- Bali